PENGARUH MEDIA PEMBELAJARAN PERMAINAN MONOPOLI TERHADAP HASIL BELAJAR IPS TERPADU DI SMPN 3 SATU ATAP BOYAN TANJUNG - Dessy Triana Relita; Karnia Karnia (STKIP Persada Khatulistiwa Sintang, 2021)
The problem in this research is that the students' activity in the class is still lacking and there are students who have low learning outcomes. The purpose of this study was to determine the effect of using monopoly game learning media on Integrated Social Studies learning outcomes. This research method uses quantitative research with a quasi-experimental approach and the form of research uses experimental research. The sample in this study consisted of 20 students in class VII A as the experimental class and class VII B with 20 students as the control class. Techniques and data collection tools using observation sheets, test questions and documentation. The results of this study indicate that there is an effect of using monopoly game learning media on the learning outcomes of Integrated Social Studies for seventh grade students at SMPN 3 Satu Atap Boyan Tanjung. The results of the pretest and posttest calculations in the experimental class, the value of sig (2-tailed) = 0.000 is smaller than 0.05, it means that H0 is rejected. Ha is accepted. Pretest and posttest in the control class, the value of sig (2-tailed) = 0.000 is smaller than 0.05, it means that H0 is rejected. Ha is accepted at a significance level of 5%.